CREATIVE WRITING AND INNOVATIVE PROCESS OF BEOWULF VIRTUAL DRAMA UNDERGRADUATE STUDENTS - Karwandi Karwandi; Rita Inderawati; Didi Suhendi; Margaretha Dinar Sitinjak; Eryansyah Eryansyah; Sardianto Markos Siahaan (University of Kuningan, 2022)
Pandemic Covid-19 forced education sector to have no more face-to-face classes since 2020. Unluckily, students from drama classes no longer performed on the stage even though they have well-prepared for the performance. This article highlighted four main problems: 1) How creative were students in writing drama script for virtual drama performance? 2) What were innovative processes created by the students for virtual drama performance? 3) What were the problem faced by the students in writing drama script and performing virtual drama performance? and 4) How were the lecturers’ role for the students in writing drama script and performing virtual drama performance? To answer these questions, the study employed online observation, interview, and documentation to dig up the research questions. The result of the study showed that by using documented-limited creative writing, most of the students were able in creating the drama script collaboratively and they utilized Zoom platform and Canva application through these preliminary investigation, detailed investigation, development, testing and validation, and full production processes. As a whole, the students were creative and innovative during the process of virtual drama performance and it could make the process of teaching and learning are worthwhile because lecturers and students had collaborated very well.